Comparative analysis of the Eastern European countries as participants of the new silk road - Nazarko, Joanicjusz; Czerewacz-Filipowicz, Katarzyna; Kuźmicz, Katarzyna Anna (Journal of Business Economics and Management, 2017)
The chinese one belt one road (obor) initiative often referred to as the new silk road (nsr), seems to be the greatest endeavour of our times in terms of economy, politics and logistics. the study aimed to examine the potential of poland, belarus, lithuania, latvia, estonia and russia to participate in the nsr. the method applied was comparative analysis including both quantitative and qualitative studies. the juxtaposition of data from the intensity of global integration enabled assessment of the potential negative consequences of non-participation of the countries in the nsr. in turn, the analysis of specific indicators of trade integration, the intensity of global integration and the logistics performance of the researched part of europe has made it possible to answer the question about the most promising variants of the nsr.